2006
DOI: 10.1093/toxsci/kfj099
|View full text |Cite
|
Sign up to set email alerts
|

Research Strategies for Safety Evaluation of Nanomaterials. Part VI. Characterization of Nanoscale Particles for Toxicological Evaluation

Abstract: To properly assign mechanisms or causes for toxic effects of nanoscale materials, their properties and characteristics both outside and within the biological environment must be well understood. Scientists have many tools for studying the size, shape, and surface properties of particulates outside of the physiological environment; however, it is difficult to measure many of these same properties in situ without perturbing the environment, leading to spurious findings. Characterizing nanoparticle systems in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
290
0
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(314 citation statements)
references
References 32 publications
3
290
0
13
Order By: Relevance
“…Besides the preparation and characterization of the suspension, comprehensive powder characterization is essential for further investigations [20]. Concerning their powder properties, hydrophilic ZnO-hydro and hydrophobic ZnOlipo were very similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the preparation and characterization of the suspension, comprehensive powder characterization is essential for further investigations [20]. Concerning their powder properties, hydrophilic ZnO-hydro and hydrophobic ZnOlipo were very similar.…”
Section: Discussionmentioning
confidence: 99%
“…The link between protein corona and ZnO, particularly in view of its solubility should be further investigated. All in all, comprehensive characterization of the materials used is necessary for interpretation of toxicological results, as mentioned in numerous reviews [3,[20][21][22]. Especially the behavior of nanoparticles under physiological conditions must be considered to fully understand the interactions with components of the culture media [20].…”
Section: Introductionmentioning
confidence: 99%
“…their size, size distribution, shape, state of dispersion, physical and chemical properties, surface area and porosity, surface chemistry) and by cell characteristics (e.g. cell line, number of cells per well, and the period of culture before and/or after exposure to nanoparticles) 17,[24][25][26]29,30) . A recent study showed a decrease in MC3T3-E1 cell viability after exposure to Ag-NPs using the WST-8 assay 31) , but this study used different test conditions for cell culture and exposure to Ag-NPs, which may explain the disparity between their results and ours.…”
Section: Discussionmentioning
confidence: 99%
“…Total Suspended Solids (TSS) are those solids in supracolloid and settleable size ranges. microscopy, and surface area measurements showed that the dynamic light scattering approach was preferred for nanoparticle size distribution testing in an aqueous environment (Powers et al, 2006). Section 3.1 and 3.2 discuss produced water sampling methods and suspended solid isolation protocols.…”
Section: Production Solidsmentioning
confidence: 99%